SUPERVISION OF LOCAL PEOPLE'S REPRESENTATIVE BOARDS IN CLEAN LOCAL GOVERNANCE GOVERNANCE - Mhd. Taufiqurrahman; Muhammad Dias Saktiawan (Jurnal Pembaharuan Hukum, 2022)
The purpose of this study is to find out about the supervision carried out by the Regional House of Representatives, one of which is the performance of the local government apparatus, namely by supervising the Regional Revenue and Expenditure Budget that has been determined and carried out by the regional government apparatus. The approach method used uses a normative juridical approach, the results of the study state that the position of the Regional People's Representative Council in the structure of the Regional Government is as a people's representative institution in the region, and at the same time as an element of regional government administrators. The form of supervision in terms of preventing the occurrence of irregularities in the use of regional budgets is by determining targets and standards for supervision related to concrete matters, for example monitoring and observing the implementation of projects carried out in one fiscal year, and further responding to public complaints against irregularities use of local budgets.